2020
DOI: 10.1038/s41598-020-57884-0
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-Seq reveals novel genes and pathways associated with hypoxia duration and tolerance in tomato root

Abstract: Due to climate change, economically important crop plants will encounter flooding periods causing hypoxic stress more frequently. this may lead to reduced yields and endanger food security. As roots are the first organ to be affected by hypoxia, the ability to sense and respond to hypoxic stress is crucial. At the molecular level, therefore, fine-tuning the regulation of gene expression in the root is essential for hypoxia tolerance. Using an RnA-Seq approach, we investigated transcriptome modulation in tomato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 89 publications
(83 reference statements)
1
44
1
Order By: Relevance
“…However, whether ethylene also contributes to metabolic hypoxia acclimation and if this correlates with flooding tolerance in these Solanum species is currently unknown. Several studies showed that genes involved in ethylene signaling and ethanolic fermentation are induced in response to flooding and hypoxia, but not consistently across all plant tissues in these Solanum species [37,40,41,45,46].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether ethylene also contributes to metabolic hypoxia acclimation and if this correlates with flooding tolerance in these Solanum species is currently unknown. Several studies showed that genes involved in ethylene signaling and ethanolic fermentation are induced in response to flooding and hypoxia, but not consistently across all plant tissues in these Solanum species [37,40,41,45,46].…”
Section: Introductionmentioning
confidence: 99%
“…The current study represents the comparative transcriptome modulation of tomato (cv. Moneymaker) root in response to long-term (48 h) hypoxia 53 and SNP-application. Long-term hypoxia, but not SNP-treatment, resulted in significantly (P < 0.05) lower root fresh weight and chlorophyll content (SPAD values) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Plant age and growth condition was the same for both hypoxia and SNP studies. The hypoxia treatment has been previously described in details 53 . Tomato plants (Solanum lycopersicum L. cv.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations